Analysis of the Establishment Procedure of the Indonesian Tabur Kasih Anak Foundation - Fauziah Agustini; Aisya Isnur Hafni; Dinda Azahra; Meli Adora Mahulae; Dicky Hebron Ginting (Formosa Journal of Applied Sciences, 2023)
A foundation is a legal entity where the purpose of the legal entity is for social, religious and humanitarian purposes. This institution was established with conditions that have been regulated and its existence has been recognized by the community and the State. In Indonesia, the establishment of a foundation is regulated in Law number 28 of 2004 and has now been updated, namely in Law number 16 of 2001, in Law number 28 of 2004 and also Law number 16 of 2001, not only in the form of rules but also of a coercive nature. The Orphanage is a place to care for orphaned children. But it's not only orphans in the orphanage, there are also children who have been abandoned by their parents. Like a victim of parental divorce. The Orphanage is sheltered by a foundation.